Dampak Pameran Pekan Kebudayaan Terhadap Literasi Budaya - Bakkara, Viona Febiyola (Nazharat: Jurnal Kebudayaan, 2024)
The Cultural Week Exhibition on Cultural Literacy is an event or activity held to exhibit, introduce, and celebrate various aspects of the culture of a region, nation, or community as a form of awareness to be literate against crocodiles. The purpose of the research is to analyze the definition and components of cultural literacy based on existing literature, as well as how this concept is applied in the context of cultural exhibitions. This research uses a literature review research method with the technique of reading and studying various journals, books, and various published manuscripts, and then systematic selection and analysis of data. Then relevant and high-quality data will be selected as results for the research. The results of the research are that cultural exhibitions can increase public awareness of the importance of preserving local culture, as well as maintain cultural identity, and encourage active participation in cultural activities. Cultural exhibitions not only function as a forum to build solidarity but also form an appreciation for cultural diversity. Then relevant and high-quality data will be selected as results for the research.